Design of Bacterial Strain-Specific qPCR Assays Using NGS Data and Publicly Available Resources and Its Application to Track Biocontrol Strains - Hernández, Iker; Sant, Clara; Martínez, Raquel; Fernández, Carolina (Frontiers in Microbiology, 2020)
Biological control is emerging as a feasible alternative to chemical pesticides in agriculture. Measuring the microbial biocontrol agent (mBCA) populations in the environment is essential for an accurate risk assessment and to optimize the usage of an mBCA-based plant protection product. In this manuscript, a workflow to obtain a large number of qPCR markers suitable for robust strain-specific detection and quantification is presented. The workflow starts from whole genome sequencing data and consists on (i) identifying the strain-specific sequences, (ii) designing specific primer/probe sets for qPCR assays, and (iii) empirically verifying the performance of the assays. The first two stages involve exclusively computer work, but they are intended for researchers with little or no bioinformatic background: only knowledge of the BLAST suite tools and working with spreadsheets are required, and familiarity with the Galaxy environment and next-generation sequencing concepts are strongly advised. All bioinformatic work can be implemented using publically available resources and a regular desktop computer, no matter the operating system, connected to the Internet. The workflow was tested with 5 bacterial strains from different species under development as mBCAs, and yielded thousands of candidate markers and a triplex qPCR assay for each candidate mBCA. The qPCR assays were successfully tested in soils of different nature, water from different sources, and samples from different plant tissues. The mBCA detection limits and population dynamics in the different matrices are similar to those in qPCR assasys designed by other means. In summary a new accessible, amenable, cost-effective and robust, workflow to obtain a large number of strain-specific qPCR markers, is presented.